Adaptation of a Muslim Spiritual Attachment Scale (God attachment) for Turkish Muslims: a validity and reliability study - Yildiz, Murat (Mental health, religion & culture, 2019)
Despite the importance of a believer’s attachment relationship with God for mental health, there are few measures relevant to Muslims, and little work on cross-cultural validation of such measures. The objective of the present study was to examine the validity and reliability of the Muslim Spiritual Attachment Scale (M-SAS) in Turkish Muslim samples. In analyzing the data, three different samples of college students (N = 525, N = 341, and N = 47 respectively) were used. The validity and reliability of M-SAS were examined through exploratory factor analysis, confirmatory factor analysis, the internal consistency coefficient and the split-half reliability coefficient. Results supported a three-factor model of M-SAS with good reliability for the factors, and convergence with an alternative God Attachment measure. As a result, it may be concluded that M-SAS can be used as a valid and reliable measurement instrument in Turkish Muslim samples. The results are discussed in the light of the relevant literature.